Relationship Between Thermal Conductivity, Mineral Composition and Major Element Composition in Rocks from Central and South Germany - Oliver Suft; Hannes Hagenauer; David Bertermann (Geosciences)
Thermal conductivity is a decisive parameter in all geothermal applications. In addition to the influencing factors of density, saturation, porosity, temperature and pressure, it is, above all, the geochemical and mineralogical composition that determines the thermal conductivity in rocks and soils. This study focuses on selected rock samples from Southern and Central Germany regarding major element oxides and minerals as well as distributed thermal conductivity. We examined clastic and chemical sedimentary, as well as igneous and metamorphic rocks, ranging from the Paleozoic to Cenozoic age. Measurements were conducted by X-ray fluorescence analysis (XRF), X-ray diffraction (XRD) and optical scanning with a thermal conductivity scanner (TCS). The results show significant correlations between thermal and geochemical parameters. Chemical composition significantly impacts thermal conductivity. Higher quartz and SiO2 contents generally lead to increased thermal conductivity, while aluminum silicates, common in clay minerals, correlate with lower conductivity. For carbonates, increased density or reduced porosity enhances conductivity. Structural differences and differing mineral concentrations influence the measurement variability along the sampling axis. This is especially visible in clastic sedimentary rock samples, where porosity decreases while cementation of the matrix increases thermal conductivity.